Proust & Signs: The Complete Text - Deleuze, Gilles 1925-1995 (Minneapolis, MN University of Minnesota Press, 2000)
In a remarkable instance of literary and philosophical interpretation, the incomparable Gilles Deleuze reads Marcel Proust's work as a narrative of an apprenticeship-more precisely, the apprenticeship of a man of letters. Considering the search to be one directed by an experience of signs, in which the protagonist learns to interpret and decode the kinds and types of symbols that surround him, Deleuze conducts us on a corollary search-one that leads to a new understanding of the signs that constitute A la recherche du temps perdu.In Richard Howard's graceful translation, augmented with an essay that Deleuze added to a later French edition, Proust and Signs is the complete English version of this work. Admired as an imaginative and innovative study of Proust and as one of Deleuze's more accessible works, Proust and Signs stands as the writer's most sustained attempt to understand and explain the work of art.Gilles Deleuze (1925-1995) was professor of philosophy at the University of Paris, Vincennes-St. Denis. With Félix Guattari, he coauthored Anti-Oedipus (1983) and A Thousand Plateaus (1987). Among his other works are Cinema 1 (1986), Cinema 2 (1989), Foucault (1988), The Fold (1992), Essays Critical and Clinical (1997), and Francis Bacon (2003), all published by the University of Minnesota Press.Richard Howard has received the American Book Award and the PEN Translation Medal. He teaches in the School of the Arts at Columbia University.
Keywords: Proust, Marcel -- 1871-1922; 20th Century (1901-2000); Philosophy; Literature; Semiotics; France